2021
DOI: 10.1186/s13756-021-00930-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness of multidrug resistant Escherichia coli isolated from humans, chickens and poultry environments

Abstract: Background Inappropriate use of antimicrobial agents in animal production has led to the development of antimicrobial resistance (AMR) in foodborne pathogens. Transmission of AMR foodborne pathogens from reservoirs, particularly chickens to the human population does occur. Recently, we reported that occupational exposure was a risk factor for multidrug-resistant (MDR) Escherichia coli (E. coli) among poultry-workers. Here we determined the prevalence and genetic relatedness among MDR E. coli is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 53 publications
8
57
1
Order By: Relevance
“…In line with our observations, other studies have reported high MDR levels in E. coli through the food chain [ 13 , 17 , 18 , 19 , 20 ]. Overall, E. coli MDR levels were reported at 76% for pig production in South Africa; 75% on farms and 50% in slaughterhouses; 72% from pig and chicken samples in Malaysia; 78% in broiler products from retail in Bangladesh with AMR above 80% to PEN, TET, and MAC; and 92% from chicken samples in Nigeria with resistance in more than two thirds to AMN, F(Q), PEN, TET, and SLP/TMP [ 17 , 18 , 19 , 20 ]. E. coli MDR was observed to differ considerably across EU member states, ranging from 3% to 85% in pigs, 0% to 87% in broilers, and 0% to 78% in turkeys.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our observations, other studies have reported high MDR levels in E. coli through the food chain [ 13 , 17 , 18 , 19 , 20 ]. Overall, E. coli MDR levels were reported at 76% for pig production in South Africa; 75% on farms and 50% in slaughterhouses; 72% from pig and chicken samples in Malaysia; 78% in broiler products from retail in Bangladesh with AMR above 80% to PEN, TET, and MAC; and 92% from chicken samples in Nigeria with resistance in more than two thirds to AMN, F(Q), PEN, TET, and SLP/TMP [ 17 , 18 , 19 , 20 ]. E. coli MDR was observed to differ considerably across EU member states, ranging from 3% to 85% in pigs, 0% to 87% in broilers, and 0% to 78% in turkeys.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our observations, other studies have reported high MDR levels in E. coli through the food chain [13,[17][18][19][20]. Overall, E. coli MDR levels were reported at 76% for pig production in South Africa; 75% on farms and 50% in slaughterhouses; 72% from pig and chicken samples in Malaysia; 78% in broiler products from retail in Bangladesh with AMR above 80% to PEN, TET, and MAC; and 92% from chicken samples in Nigeria with resistance in more than two thirds to AMN, F(Q), PEN, TET, and SLP/TMP [17][18][19][20]. E. coli MDR was observed to differ considerably across EU member states, ranging from 3% to 85% in pigs, 0% to 87% in broilers, and 0% to 78% in turkeys.…”
Section: Discussionsupporting
confidence: 93%
“…High resistance rates were observed in all isolates, especially to aminoglycosides, cephalosporins, penicillins, quinolones, and trimethoprim + sulfamethoxazole. Two isolates were also resistant to carbapenems, which was also observed recently in Nigeria ( Aworh et al, 2021 ), and four were resistant to amphenicol. The high degree of AMR in our study is not surprising, as these antibiotics (ceftriaxone, ciprofloxacin, and beta-lactamases) are easily accessible and commonly used in Benin for therapeutic purposes and very few antimicrobial stewardship programs are in place.…”
Section: Discussionsupporting
confidence: 83%
“…The presence and persistence of resistance in commensal E. coli is a significant biomarker for the selective pressure enforced by antibiotic use and subsequent resistance predicted in other potentially pathogenic bacteria [ 20 ]. The high prevalence of MDR E. coli in poultry has been evaluated and reported in several countries including Nigeria [ 5 , 21 , 22 , 23 , 24 , 25 ]. However, only a few studies on MDR E. coli among chickens in LBMs in the country exist.…”
Section: Introductionmentioning
confidence: 99%